From Berlin to Istanbul: The First Balkan Passengers of the Ottoman-German Alliance - Yusuf Ziya ALTINTAŞ (Journal of Balkan Studies)
At the beginning of World War I, the Ottoman Empire and Germany signed a secret alliance treaty, which obligated Germany to protect Ottoman territories. Although the Ottoman government initially declared neutrality, it had committed to joining the war on Germany’s side once mobilization was complete. This necessitated strengthening the defense of strategic locations, particularly the Bosporus and Dardanelles. At the same time, the Ottoman Navy had to be reinforced. In August 1914, to fortify the straits and navy, more than 500 German military and technical personnel, led by Admiral Guido von Usedom, were secretly transported to Istanbul via the Balkans. To avoid attracting attention, the journey was conducted under civilian disguise with careful planning. This operation marked the first major military deployment under the alliance and significantly increased German influence in Istanbul while the Ottoman Empire was still officially neutral. The article examines this journey through the accounts of German officers and archival documents.